NEONATAL OUTCOME WITH INSTRUMENTAL VAGINAL DELIVERY: A STUDY AT PNS SHIFA - ., Humaira Arshad; ., Shehla Baqai; Abdullah, Khalida Nasreen; ., Bushra Iftikhar (Pakistan Armed Forces Medical Journal, 2011)
Objective: To evaluate neonatal outcome in terms of Apgar score after forceps and ventouse delivery in pregnant ladies indicated to have instrumental deliveries. Study Design: Randomized control trial. Place and Duration of study: This study was conducted at Labor ward of department of obstetrics & gynecology, PNS SHIFA Karachi, between Dec 2007 to Mar 2008. Subjects and Methods: The target population were all pregnant subjects who visited labor room for delivery. Out of these patients, subjects who were indicated an assisted vaginal delivery for necessary management of labor were formally requested to participate in the study after various exclusions. Instrumentation was done in only those patients with singleton term pregnancy with cephalic presentation and vertex at + 1 to +3 stations. Patients with an indication for assisted vaginal delivery (n=105), were randomized for ventouse (n=53) and forceps delivery (n=52). Instruments used were Wrigley’s outlet forceps and vacuum extractor (V.E) with silicone cups. Data was recorded on specially designed Proforma. Post delivery neonatal outcome in terms of Apgar score at one minute and five minutes were compared between two modalities. Results: The subjects undergoing forceps delivery had a significantly higher Apgar score (8.36±1.27) at 1 minute in comparison to those subjected to vacuum delivery (7.53±1.56). The differences in Apgar score at 5-minutes (forceps delivery: 9.136 + 1.01 vs vacuum delivery 9.00 + 1.19), were not statistically significant. Conclusion: Outlet forceps assisted vaginal deliveries had better neonatal outcome in terms of Apgar score in comparison to ventouse.